2012
DOI: 10.3390/toxins4121565
|View full text |Cite
|
Sign up to set email alerts
|

Sheep Monoclonal Antibodies Prevent Systemic Effects of Botulinum Neurotoxin A1

Abstract: Botulinum neurotoxin (BoNT) is responsible for causing botulism, a potentially fatal disease characterized by paralysis of skeletal muscle. Existing specific treatments include polyclonal antisera derived from immunized humans or horses. Both preparations have similar drawbacks, including limited supply, risk of adverse effects and batch to batch variation. Here, we describe a panel of six highly protective sheep monoclonal antibodies (SMAbs) derived from sheep immunized with BoNT/A1 toxoid (SMAbs 2G11, 4F7) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
(36 reference statements)
0
8
0
Order By: Relevance
“…While human patients report early botulism symptoms such as blurred vision, dry mouth, and diplopia or just odd feelings long before the appearance of observed signs such as ptosis and difficulty speaking (19), animals, especially rodents, do not present such facial symptoms and obviously cannot report their situation. As a consequence, the use of antitoxin in animal studies has been related mostly to time postintoxication, whereas data regarding treatment after the onset of symptoms have been collected only post factum (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). To the best of our knowledge, only a few attempts to directly measure postsymptom antitoxin efficacy were reported, mostly for BoNT/A-intoxicated nonhuman primates (14,(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While human patients report early botulism symptoms such as blurred vision, dry mouth, and diplopia or just odd feelings long before the appearance of observed signs such as ptosis and difficulty speaking (19), animals, especially rodents, do not present such facial symptoms and obviously cannot report their situation. As a consequence, the use of antitoxin in animal studies has been related mostly to time postintoxication, whereas data regarding treatment after the onset of symptoms have been collected only post factum (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). To the best of our knowledge, only a few attempts to directly measure postsymptom antitoxin efficacy were reported, mostly for BoNT/A-intoxicated nonhuman primates (14,(39)(40)(41)(42).…”
Section: Discussionmentioning
confidence: 99%
“…While antitoxin is administered to patients only after symptom onset, its use in animal studies has been related mostly to time postintoxication regardless of symptoms (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). To evaluate antitoxin efficacy in a more clinically relevant timeline of treatment, we recently developed a mouse model for postsymptom, antibotulinum therapy (33).…”
mentioning
confidence: 99%
“…Similarly, six highly protective sheep mAbs (SmAbs) derived from sheep immunized with BoNT/A1 toxoid or BoNT/A1 HCc have been generated. Divalent and trivalent combinations of the SmAbs, were highly protective and the trivalent combination was 100% protective against experimental clinical signs and death, reflecting protective levels not reported previously [72]. MAbs are also effective for immuno-affinity purification and concentration of BoNTs from complex matrices such as clinical samples in the mass spectrometry-based method [73].…”
Section: Generation Of Mouse Sheep or Humanized Monoclonal Antibomentioning
confidence: 87%
“…Co-administration of the targeting agent and the clearing antibody resulted in decoration of the toxin with up to four antibodies to promote accelerated clearance. Surprisingly, when a post-intoxication treatment model was used, a toxin-neutralizing heterodimer agent fully protected mice from intoxication even in the absence of clearing antibody [72]. However, antibodies targeting the proteolytic domain of the toxin can inhibit the proteolytic activity of the toxin intracellularly and potentially reverse intoxication, if they can be delivered intracellularly.…”
Section: Alternative Strategies For Improvement Of Mabs Neutralizamentioning
confidence: 99%
“…The resulting toxin clearance dramatically enhanced the protection of mice from virtually no protection in the absence of the clearing Fc to complete protection against 1000 MsLD 50 of BoNT/A. Furthermore, a comparison of the antitoxin efficacy between neutralizing and non-neutralizing VHH agents in the presence or absence of the anti-tag clearing Fc revealed that the neutralizing VHHs were highly effective in the absence of clearance (and were improved in the presence of the clearing Fc), whereas non-neutralizing VHHs depended on the clearing Fc for efficient neutralization [ 23 ].…”
Section: Synergistic Neutralization Of Mab Cocktailsmentioning
confidence: 99%